(untitled) (Revista Científica Compendium, 2018)
The relationship between Church and State today can not be clearly studied if there is at least a basic knowledge of the history of the Colonial State and the Church of the time. That is why we want to contribute with this brief essay, ananalys is that covers the fundamental characteristics, beginning with the establishment of the Church in America and the process of its implementation in Venezuelan territory, which we expose as an interrelation between Church and royal policy. We then analyze the establishment of the tribunals in America and the subsequent activity of the Royal Audiencia of Caracas in relation to the evangelizing function of the clergy. This results in a study based on primary sources that provides a contribution to the studies of a historical nature on the judicial theory of theVenezuelan State, under a qualitative approach.